The linguistic vision of Ibn Janni in the "Alkhasaes" A new reading in light of the contemporary linguistic lesson - Yassen, Malek (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
There are many linguistic researches and studies that concerned Ibn Janni, some of which were devoted to his knowledge, culture and literature. Another section was devoted to Ibn Janni Al-Nhawi, and his implications in this field. Other studies were devoted to the treatment of morphological aspects in his books, In his books in general, and in his book " Alkhasaes " in particular. But this study will mean a new aspect has not been highlighted in previous studies and research, although the title suggests the similar scientific tracks between them and previous studies, but this study is characterized by contain new scientific trends that appear to the student by talking about: In the new book that possesses visions and explores the ideas, reflections and interpretations of the study, and the course of the study to two main tracks; the first theoretical summits views and issues and presents them objectively, and the other analytical brings to the selected examples and evidence, Conducted in analytical paths applied, and then the study tries to explore the prestige enjoyed by the thought of Ibn taking language and vision in contemporary language studies.